Human Serum Antibodies to a Major Defined Epitope of Human Herpesvirus 8 Small Viral Capsid Antigen - Tedeschi, Rosamaria; De Paoli, Paolo; Schulz, Thomas F.; Dillner, Joakim (The Journal of infectious diseases, 1999)
The major antibody-reactive epitope of the small viral capsid antigen (sVCA) of human herpesvirus 8 (HHV-8) was defined by use of overlapping peptides. Strong IgG reactivity was found among ∼50% of 44 human immunodeficiency virus-positive or -negative patients with Kaposi's sarcoma and 13 subjects who were seropositive by immunofluorescence assay (IFA) for the latent HHV-8 nuclear antigen. Only 1 of 106 subjects seronegative for both lytic and latent HHV-8 antigens and 10 of 81 subjects IFA-seropositive only for the lytic HHV-8 antigen had strong IgG reactivity to this epitope. Among 534 healthy Swedish women, only 1.3% were strongly seropositive. Comparison of the peptide-based and purified sVCA protein-based ELISAs found 55% sensitivity and 98% specificity. However, only 1 of 452 serum samples from healthy women was positive in both tests. In conclusion, the defined sVCA epitope was a specific, but not very sensitive, serologic marker of active HHV-8 infection. Such infection appears to be rare among Swedish women, even with sexual risk-taking behavior.